Treatment of a Chronic Galeazzi Fracture-dislocation. A Case Report - Yaniel Truffin Rodríguez; Rafael López Cuéllar; Osmany Pérez Martínez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2016)
Galeazzi fracture-dislocation is a rare injury that may go unnoticed. It should be suspected when dealing with a displaced fracture of the junction of the distal and middle third of the radial shaft. For these reasons, we present the case of a 50-year-old patient who suffered a trauma with a cutting tool in the junction of the distal and middle third of his left forearm, which resulted in a wound on the dorsal aspect of the forearm and a Galeazzi fracture-dislocation. We could not determine whether the fracture had been open or not since the patient did not provide clear information during the assessment conducted in the Orthopedics Service of the hospital of Cienfuegos 55 days after the trauma. The open reduction and internal fixation of the fracture was performed. Given the time elapsed since the injury and the presence of degenerative lesions in the wrist, a distal radioulnar arthrodesis (the Sauvé-Kapandji procedure) was carried out. The stabilization of the distal ulna was achieved by using a 3.5 mm malleolar screw placed in an ulnar to radial direction. The patient underwent physical rehabilitation and was discharged five months later with satisfactory results.